2012
DOI: 10.1177/0020852312445172
|View full text |Cite
|
Sign up to set email alerts
|

Integrity management and the public service ethos in the UK: patchwork quilt or threadbare blanket?

Abstract: This paper focuses on the nature of integrity management in contemporary UK public life. Despite traditionally high standards of integrity in the public service, it has recently been argued that the UK's National Integrity System resembles a patchwork quilt of poorly defined institutional roles, questionable independence, and contested notions of how best to disseminate and uphold ethical practice. The paper traces how a relatively enduring characteristic known as the British public service ethos (PSE), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the United Kingdom, the capacity of political elites to control the implementation phase through patronage is much weaker. Appointments to the civil service are meritocratic and mainly non-political (Heywood 2012), with the exception of special advisers (Yong and Hazell 2014). There is little change in personnel when governments change, and our interviews suggested that the institutional structures for implementing and monitoring public procurement are much less prone to political influence.…”
Section: Institutional Controls In Hungarymentioning
confidence: 99%
“…In the United Kingdom, the capacity of political elites to control the implementation phase through patronage is much weaker. Appointments to the civil service are meritocratic and mainly non-political (Heywood 2012), with the exception of special advisers (Yong and Hazell 2014). There is little change in personnel when governments change, and our interviews suggested that the institutional structures for implementing and monitoring public procurement are much less prone to political influence.…”
Section: Institutional Controls In Hungarymentioning
confidence: 99%
“…Rules-based approaches provide clear guidelines and may be straightforward and quick to implement and monitor, not least after ethics scandals when they often are the go to solution, but responses in these situations are often improvised rather than well thought through (Anechiarico & Jacobs, 1996; Demmke & Moilanen, 2011, p. 43; Heywood, 2012, p. 478). However, in large organizations with many tasks and activities, it is impossible to regulate every aspect of an organization and its activities (Hoekstra et al, 2008).…”
Section: Theory and Framework Of Analysismentioning
confidence: 99%
“…IP planning is a matter of wholeness, because it connects ambitions to concrete targets and outcomes. Without a clear plan and set targets, integrity activities are destined to remain rather incident-driven (Van Der Wal, Graycar, & Kelly, 2016), prompted by scandals (Heywood, 2012), or impelled by erratic political or financial decisions (Lawton, Rayner, & Lasthuizen, 2013). Thus, as a matter of wholeness, IP planning entails firstly (4.1.1) specifying the program's ambitions and targets in a plan.…”
Section: Processual Wholenessmentioning
confidence: 99%